HUBUNGAN FUNGSI KOGNITIF TERHADAP ACTIVITY OF DAILY LIVING (ADL) PADA PASIEN PASCA STROKE: The Relationship Between Cognitive Function and Activities of Daily Living (ADL) in Post-Stroke Patients - Corolla, Anjelly; Saputra, Bayu; Abdur Rasyid, T. (JURNAL KESEHATAN KARTIKA, 2025)
Background: Post-stroke patients often experience cognitive impairment that can affect their ability to perform activities of daily living (ADL). Cognitive function plays an important role in supporting patients' independence in their daily lives. Impairment of this function can affect patients' ability to plan, remember, solve problems, and make decisions, thereby increasing their dependence on others and reducing their quality of life. Therefore, early identification and intervention of post-stroke cognitive impairment are essential to maximize recovery and improve patient independence. Objective : This study aims to analyze the relationship between cognitive function and ADL ability in post-stroke patients. Method : This study is a quantitative study with a cross-sectional design. This study was conducted using non-probability sampling with consecutive sampling. The sample in this study consisted of 30 respondents. The analysis used was univariate analysis with central tendency and frequency distribution as well as bivariate analysis using the person chi-square test. Result : The results of the analysis showed that the majority of respondents who had suffered a stroke were 58.97 years old, 17 respondents (56.7%) were male, 16 respondents (53.3%) had a high school education or equivalent, 22 respondents (72.2%) had ischemic stroke, 19 respondents (63.3%) had severe cognitive impairment, and 11 respondents (36.7%) had mild ADL dependence. The results of bivariate analysis using the Person Chi-Square test obtained a p-value of 0.098 (<0.05). conclusion : The results of this study can be concluded that there is no significant relationship between cognitive function and Activities of Daily Living (ADL) in post-stroke patients. Further research is recommended to explore the relationship between the level of cognitive impairment and ADL ability in post-stroke patients, as well as to identify factors that influence cognitive function recovery